Developing a holistic strategy for integrated waste management within municipal planning: challenges, policies, solutions and perspectives for Hellenic municipalities in the zero-waste, low-cost direction - Zotos, Yorgos; Karagiannidis, Avraam K.; Zampetoglou, S.; Malamakis, Apostolos; Antonopoulos, Ioannis Sofocles; Kontogianni, Stamatia; Tchobanoglous, George (My University, 2009)
The present position paper addresses contemporary waste management options, weaknesses and opportunities faced by Hellenic local authorities. It focuses on state-of-the-art, tested as well as innovative, environmental management tools on a municipal scale and identifies a range of different collaboration schemes between local authorities and related service providers. Currently, a policy implementation gap is still experienced among Hellenic local authorities; it appears that administration at the local level is inadequate to manage and implement many of the general policies proposed; identify, collect, monitor and assess relevant data; and safeguard efficient and effective implementation of MSWM practices in the framework of integrated environmental management as well. This shortfall is partly due to the decentralisation of waste management issues to local authorities without a parallel substantial budgetary and capacity support, thus resulting in local activity remaining often disoriented and isolated from national strategies, therefore yielding significant planning and implementation problems and delays against pressing issues at hand as well as loss or poor use of available funds. This paper develops a systemic approach for MSWM at both the household and the non-household level, summarizes state-of-theart available tools and compiles a set of guidelines for developing waste management master plans at the municipal level. It aims to provide a framework in the MSWM field for municipalities in Greece as well as other countries facing similar problems under often comparable socioeconomic settings.
Keywords: Decentralisation; Environmental management tools; Household levels; Integrated environmental managements; Integrated waste managements; Local activities; Local authorities; Management issues; Master plans; National strategies